Aechmea blanchetiana - Edward F. Gilman (EDIS, 2004)
The attractive orange foliage with red tips of this easy-care bromeliad is a perfect background for the brilliant, springtime flower stalk, which emerges from the tight center rosette of leaves. The flower stalk is composed of a cluster of red and yellow showy bracts. It is the long-lasting bracts that are most noticeable. They can be used as cut flowers indoors for a period of weeks.  This document is Fact Sheet FPS-14, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: October 1999. Reviewed October 2003.